Evaluasi SPO Pengujian Produk Jadi Pre-Marketing terhadap Mutu Sediaan COL (Cairan Obat Luar) Tradisional di Salah Satu Industri X - Farmani, Komang Tri; Warditiani, Ni Kadek (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 12 No 2 (2022): Indonesian Journal of Legal and Forensic Sciences, 2022)
Introduction: The traditional medicine industry (TMI) is an industry that can produce all types of traditional medicinal preparations including EML (external medicine liquid). In the process of making traditional medicine (TM), TMI is obliged to follow the rules of GMPTM (good manufacturing practices traditional medicines) which aims to ensure the quality of the preparations produced. In the process, an SOP (standard operating procedure) is needed which contains the steps that must be taken to realize the goals and product quality (specifications) that have been determined. Pre-marketing finished product testing is part of the production process, so it also requires an SOP. One of the IOT X that has made CML has been established long time, of course it already has a Finished Products Pre-Marketing EML Preparations Testing SOP . Objective: to evaluate the SOP of Pre-Marketing Finished Product Testing on the quality of COL preparations, based on quality standards finished products which are regulated in BPOM Regulation No. 32 of 2019 concerning the Safety and Quality Requirements for Traditional Medicine and 1996 SNI (Indonesian National Standard), and GMPTM 2021. Methods: literature study and observational description with a qualitative approach in the form of interviews Results: SOP is in accordance with existing EML quality standards, its implementation has also been implemented well (during the production of COL X products never happened not eligible), and there has never been a recall of EML products during the production period. Conclusion: The SOP for testing finished products in the pre-marketing phase has been implemented properly in accordance with applicable regulations.